Ethical Theological Study of the Impact of Plastic Waste on Tourism Life in the GMIM Patmos Bunaken Congregation, Bunaken Region: Kajian Etis Teologi Dampak Sampah Plastik Bagi Kehidupan Pariwisata Di Jemaat GMIM Patmos Bunaken Wilayah Bunaken - Hendry Corneles Mamengko Runtuwene; Josua Cristian Caroles; Nontje M. Timbuleng (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research discusses the ethical and theological study of the impact of plastic waste on tourism life in the GMIM Patmos Bunaken Congregation, which is the most critical part, so it must be maintained and preserved as a form of our responsibility to God as written in the book of Genesis 1: 26 – 28. Moreover, this research uses qualitative research by conducting interviews at the GMIM Patmos Bunaken Congregation, Bunaken Region. Data was obtained through observation, interviews, documentation, and data analysis. The analysis results show that most congregation members already have a sense of responsibility for not throwing away plastic waste carelessly because this has a fatal impact on the beauty of tourism in Bunaken National Park. Through this research, it is hoped that members of the congregation will be more aware of how important it is to protect and preserve God's creation and also know that throwing away plastic waste carelessly will hurt the environment, health, and even the economy of the congregation.